Antibody-mediated rejection: prevention, monitoring and treatment dilemmas. Issue 5 (11th October 2022) - Rodriguez-Ramirez, Sonia; Al Jurdi, Ayman; Konvalinka, Ana; Riella, Leonardo V.
Abstract : Purpose of review: Antibody-mediated rejection (AMR) has emerged as the leading cause of late graft loss in kidney transplant recipients. Donor-specific antibodies are an independent risk factor for AMR and graft loss. However, not all donor-specific antibodies are pathogenic. AMR treatment is heterogeneous due to the lack of robust trials to support clinical decisions. This review provides an overview and comments on practical but relevant dilemmas physicians experience in managing kidney transplant recipients with AMR. Recent findings: Active AMR with donor-specific antibodies may be treated with plasmapheresis, intravenous immunoglobulin and corticosteroids with additional therapies considered on a case-by-case basis. On the contrary, no treatment has been shown to be effective against chronic active AMR. Various biomarkers and prediction models to assess the individual risk of graft failure and response to rejection treatment show promise. Summary: The ability to personalize management for a given kidney transplant recipient and identify treatments that will improve their long-term outcome remains a critical unmet need. Earlier identification of AMR with noninvasive biomarkers and prediction models to assess the individual risk of graft failure should be considered. Enrolling patients with AMR in clinical trials to assess novel therapeutic agents is highly encouraged.